Imagining Transmedia (The MIT Press, 2024)
How the blurring of media forms—transmedia—became the default for how we experience narratives, and how that cultural transformation has redefined the worlds of education, entertainment, and our increasingly polarized public discourse.Over the past decade, the power of narrative has been unleashed with awesome and terrifying consequences, and it has been consumed in its blurred media forms by millions of people as news, entertainment, and education. Imagining Transmedia, edited by Ed Finn, Bob Beard, Joey Eschrich, and Ruth Wylie, explores the surprising ways that narratives working across media forms became the default grammar for both media consumption and personal expression and how multiplatform storytelling creates new media literacies and modes of civil discourse. Understanding this shift reveals transmedia as an essential building block of media literacy today. Transmedia is how we create, interpret, and participate in our increasingly mediated society. It extends beyond popular culture into professional and public spheres while, at the same time, it fuels the misinformation and polarization that have contributed to America's fraying civic discourse. Reaching beyond traditional academic analyses, this probing collection of essays and conversations features transmedia practitioners sharing their experiences and inviting readers to imagine the types of multimodal stories and experiences they might create. Prioritizing conversation over a single unified theory, each section of this volume pairs thematically linked essays from international contributors with a dialogue between authors to create an accessible, practical synthesis of ideas.